SOCIAL SKILLS DEVELOPMENT FOR PRIMARY SCHOOL STUDENTS WITH MODERATE AND SEVERE MENTAL DISABILITY AT SPECIAL BOARDING SCHOOL - Gruzdiņa, Ina (Education Reform: Education Content Research and Implementation Problems, 2019)
Primary school pupils with moderate and severe mental disabilities characterized by slow and peculiar development of cognitive processes, lack of will, interest and motivation, which makes it difficult to acquire social skills. Often, pupils with mental disabilities also experience autism spectrum disorders characterized by stereotypical behavior, lack of language communication and socialization. Considering the peculiarities of the development of pupils with moderate and severe mental disability and autism spectrum disorders, communication and socialization skills, as well as traffic accident statistics, the social skills of primary school pupils to adhere to the rules of safe behavior on the street and in public transport are becoming more important. There is a question - how to stimulate, interest students with moderate and severe mental disability and autism spectrum disorders in a more effective way in promoting the development of this social skill in a special boarding school environment based on the individual needs of students. The aim of the research is theoretically explore the possibilities of developing social skills for primary school pupils with moderate and severe mental disorders and autism spectrum disorders, to develop and test the importance of using interactive social photo stories in promoting social skills - safe behavior on the street.